Biosphere as semiosphere: Variations on Lotman - Markoš, Anton (Sign Systems Studies, 2014)
The analogy between semiosphere (world of cultures) and biosphere (world of life), coined by J. Lotman, is a courageous attempt to interconnect two seemingly incompatible worlds. In congruence with his view, I would like to convince the reader that the only possible general definition of life is “a system born, endowed with semiosis, with history”. Such a view requires considering biosphere and semiosphere as coextensive, which requires merging the cultural, scientific, historical, and linguistic approaches into a coherent whole.